Uncovering the Moral Nexus, Morality, Akhlaq, and Character in Islamic Religious Education: A Comprehensive Conceptual Analysis - Maksudin (Jurnal Pendidikan Agama Islam, 2023)
Purpose – This study aims to provide a comprehensive and novel conceptual analysis, revealing the relationship between “moral,” “morality,” “akhlaq,” and “character,” examining their similarities and differences to provide a more comprehensive understanding of their role in Islamic Religious Education (IRE). Design/methods/approach – This study uses an in-depth conceptual analysis approach, dissecting these terms through a multi-stage process: 1) an extensive literature review to understand historical and contemporary definitions, 2) a comparison of these definitions to identify similarities and discrepancies, 3) contextual exploration that considers cultural and linguistic uses in different societies, and 4) theoretical applications based on insights from functionalist theory,  Sufi psychology, and Tazkiyah theory. Findings – The study used an in-depth conceptual analysis approach, dissecting these terms through a multi-stage process: 1) an extensive literature review to understand historical and contemporary definitions, 2) a comparison of these definitions to identify similarities and discrepancies, 3) a contextual exploration that considers cultural and linguistic uses in different societies, and 4) theoretical applications based on insights from functionalist theory, Sufi psychology,  and the theory of Tazkiyah. Research implications/limitations – The study used an in-depth conceptual analysis approach, dissecting these terms through a multi-stage process: 1) an extensive literature review to understand historical and contemporary definitions, 2) a comparison of these definitions to identify similarities and discrepancies, 3) a contextual exploration that considers cultural and linguistic uses in different societies, and 4) theoretical applications based on insights from functionalist theory, Sufi psychology,  and the theory of Tazkiyah. Originality/value – The research uniquely explains key moral and ethical terms, providing valuable insights to strengthen IRE science, teaching, learning, curriculum development, and learning environments. The findings may also provide information for IRE teacher education, educational technology, learning assessment, and development education.